Actively rotating granular particles manufactured by rapid prototyping - Scholz, Christian; Pöschel, Thorsten (Revista Cubana de Fisica, 2016)
We study actively rotating granular particles manufactured by rapid prototyping. Such particles, as introduced in Ref. [1], convert vibrational motion into rotational motion via tilted elastic legs in a circular arrangement at the bottom of the particle. We extend the original design of the particles to make them suitable for mass-fabrication via rapid prototyping. The rotational velocity is measured in dependence of the driving frequency and amplitude. We find two different regimes of motion. For small amplitudes the particle performs a slow and stable rotation, while above a certain threshold the particle starts to perform a precission and consequently rotates significantly faster.